2015
DOI: 10.1136/gutjnl-2014-308617
|View full text |Cite
|
Sign up to set email alerts
|

Deep resequencing of 131 Crohn's disease associated genes in pooled DNA confirmed three reported variants and identified eight novel variants

Abstract: Our deep resequencing of 131 CD associated genes confirmed 3 reported risk loci and identified 8 novel risk loci for CD in Koreans, providing new insights into the genetic architecture of CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 58 publications
3
77
0
1
Order By: Relevance
“…We next examined the potential associations of type I Paneth cell phenotype with 56 SNPs, selected based on known CD susceptibility associations (3,5,(21)(22)(23)(27)(28)(29) or known association with Paneth cell function (17) (Supplemental Table 3). These SNPs include coding variants for ATG16L1 (T300A) associated with Paneth cell defects in North American CD cohorts and in genetic mouse models (18,19,30).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We next examined the potential associations of type I Paneth cell phenotype with 56 SNPs, selected based on known CD susceptibility associations (3,5,(21)(22)(23)(27)(28)(29) or known association with Paneth cell function (17) (Supplemental Table 3). These SNPs include coding variants for ATG16L1 (T300A) associated with Paneth cell defects in North American CD cohorts and in genetic mouse models (18,19,30).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, studying CD patients from other ethnicities, especially those who possess a spectrum of susceptibility genes distinct from those found in European ancestry CD, would be helpful in identifying novel genetic determinants of Paneth cell phenotype. The genetic landscape of CD patients from Korea and Japan is partially overlapping but largely different than that of European ancestry CD (5,(21)(22)(23). In particular, the NOD2 variants associated with European ancestry CD are not polymorphic in Japanese populations (24).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory bowel disease (IBD), including ulcerative colitis (UC) and Crohn disease (CD), are chronic, relapsing, immunemediated intestinal inflammatory diseases of complex etiology (1)(2)(3)(4), found predominantly in white people (1,3) and incurring substantial socioeconomic costs; in excess of $1.7 billion/y in Canada (5). The exact contributions of environmental factors (6), immune dysregulations (7), and genetics (8) are unknown, which impairs therapeutic success.…”
Section: Introductionmentioning
confidence: 99%
“…Genome wide association studies (GWAS) and subsequent meta-analysis for CD have identified more than 140 susceptible genes contributing to CD, such as NOD2, IL23R, ATG16L1, TNFSF15, IL17 etc. [13,14]. These researches focused on the functional relevance of genetic variations, the mechanisms of how these susceptible genes lead to the pathogenesis of CD has not been fully explained [15].…”
Section: Discussionmentioning
confidence: 99%